6(x+12)=-48

Simple and best practice solution for 6(x+12)=-48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+12)=-48 equation:


Simplifying
6(x + 12) = -48

Reorder the terms:
6(12 + x) = -48
(12 * 6 + x * 6) = -48
(72 + 6x) = -48

Solving
72 + 6x = -48

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-72' to each side of the equation.
72 + -72 + 6x = -48 + -72

Combine like terms: 72 + -72 = 0
0 + 6x = -48 + -72
6x = -48 + -72

Combine like terms: -48 + -72 = -120
6x = -120

Divide each side by '6'.
x = -20

Simplifying
x = -20

See similar equations:

| 6x+2(6x-14)=62 | | 2x^2-11=12x | | -61(x+9)=-6 | | -9(x+8)=-18 | | 6x+6(2x+2)=120 | | 3^(-9/3)+4^6*8 | | 4xsquared-100=0 | | SQRT(x^2)=x | | 5x=2x+6/7 | | SQRT(x^3)=SQRT(x^2) | | (x+7)/-6=-3 | | y/-6=-3 | | (x-9)/6=-5 | | y/6=-5 | | x-9=-30 | | sqrt(29)-x=x-9 | | g(x)=0.08x^3-3.4x^2-0.4x | | 2135/7 | | n-3n=147 | | (x-8)/3=5 | | 3-i/2+i | | (x+3)/5=4 | | 4x+2(x-5)=50 | | y/5=4 | | 0=-7x^2+5x+8 | | x^2-1000x+1000=0 | | x(3-10)= | | 6-xy=12 | | 6-x-1=12 | | 78=-5(3x+6)+2x | | 0=-5x^2+5x+3 | | 5/4y^2-625/36y-275/36 |

Equations solver categories